2018
DOI: 10.1027/1618-3169/a000390
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Deviance Distraction and the Impact of the Modality of the To-Be-Ignored Stimuli

Abstract: It has been suggested that deviance distraction is caused by unexpected sensory events in the to-be-ignored stimuli violating the cognitive system's predictions of incoming stimuli. The majority of research has used methods where the to-be-ignored expected (standards) and the unexpected (deviants) stimuli are presented within the same modality. Less is known about the behavioral impact of deviance distraction when the to-be-ignored stimuli are presented in different modalities (e.g., standard and deviants pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Distractor stimuli often lead to a decreased performance (Parmentier, 2008;Bendixen et al, 2010;Parmentier et al, 2010Parmentier et al, , 2019Demeter et al, 2016) due to increase in reaction time (Parmentier et al, 2010(Parmentier et al, , 2019, while there is evidence for both an increase (SanMiguel et al, 2010;Marsja et al, 2018) and a decrease in accuracy (Demeter et al, 2016). In contrast to the majority of these studies the multisensory alignment of our auditory and visual events led to no significant modification of reaction times, but an increase in accuracy.…”
Section: Discussionmentioning
confidence: 86%
“…Distractor stimuli often lead to a decreased performance (Parmentier, 2008;Bendixen et al, 2010;Parmentier et al, 2010Parmentier et al, , 2019Demeter et al, 2016) due to increase in reaction time (Parmentier et al, 2010(Parmentier et al, , 2019, while there is evidence for both an increase (SanMiguel et al, 2010;Marsja et al, 2018) and a decrease in accuracy (Demeter et al, 2016). In contrast to the majority of these studies the multisensory alignment of our auditory and visual events led to no significant modification of reaction times, but an increase in accuracy.…”
Section: Discussionmentioning
confidence: 86%
“…Attentional capture by deviant sounds is not contingent upon tasks taxing STM (e.g., Hughes et al., 2005, 2007; Lange, 2005) and has been shown in cross-modal task settings using auditory (e.g., Parmentier, 2014) and vibratory (Parmentier et al., 2011b; Ljungberg and Parmentier, 2012; Marsja et al., 2018) TBI stimuli. Furthermore, deviant stimuli have also been found to elicit three brain responses.…”
Section: Discussionmentioning
confidence: 97%
“…Deviant vibrations have been shown to capture attention from categorization tasks (Parmentier et al., 2011c): an effect that has been found to be functionally similar to attention capture by deviant stimuli (Ljungberg and Parmentier, 2012). Finally, it has also been reported that an omission of a standard vibration can capture attention (Marsja et al., 2018). Although bimodal deviants have been reported to capture attention using the oddball paradigm, the effect has not been found to be larger than auditory deviants (Boll and Berti, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Compared with the auditory condition, the subjects actively allocate attention to the visual-modality sentences (primary task) and the tactile-modality target (secondary and cross-modal task). Attention allocation to auditory stimuli decreased when attention was directed to sequences of tactile stimulus (Marsja et al, 2018). Neuroimaging studies also revealed that the activity of the auditory cortex is attenuated when visual stimuli are presented, while the activity of the visual cortex is attenuated when tactile or auditory stimuli are presented (Laurienti et al, 2002;Merabet et al, 2007).…”
Section: Dual Tasks and Attention Capture By Delayed Voicementioning
confidence: 96%